Infection of Ixodes ricinus ticks with Bartonella spp. in the Lublin macroregion - Zając, Violetta; Wójcik-Fatla, Angelina; Szymańska, Jolanta (Polish Journal of Public Health, 2009)
Introduction. Diseases transmitted by Ixodes ricinus ticks are naturally focal, which justifies the study on environmental conditions of the transmission of pathogens vectored by these arthropods. Aim. The aim of the study was to determine the level of infection of ticks with Bartonella spp., which is the etiological factor of cat scratch disease, Carrion’s disease and trench fever. Materials and methods. 1182 Ixodes ricinus ticks collected from five selected sites in the Lublin macroregion (Zwierzyniec, Żyrzyn, Parczew, Włodawa, Dąbrowa). To detect Bartonella spp., the polymerase chain reaction method (PCR) was applied; the genetic marker was the gltA gene encoding the citrate synthase. Results. The total percentage of infections with Bartonella spp. in the Lublin macroregion was 1.1%. The highest proportion of infections was found in ticks harvested in Dąbrowa (3.4%), while that detected in Parczew was much lower (0.9%). In three remaining study areas (Zwierzyniec, Żyrzyn, Włodawa) the gltA gene was not found in the collected ticks. The levels of infection in males and in females were similar (2.2% and 2.0%), while in nymphs Bartonella spp. gene was not detected. Conclusions. Despite the low percentage of infections with Bartonella spp. in the Lublin province (1.1%), Ixodes ricinus ticks cannot be excluded as a potential vector of this pathogen, which may be important for the appropriate diagnostics and prophylactics of tick-borne diseases